Not Good, but Not All Bad: Dehydration Effects on Body Fluids, Organ Masses, and Water Flux through the Skin of Rhinella schneideri (Amphibia, Bufonidae) - Anderson, Rodolfo C. O. [UNESP]; Bovo, Rafael P. [UNESP]; Eismann, Carlos E. [UNESP]; Menegario, Amauri A. [UNESP]; Andrade, Denis V. [UNESP] (Univ Chicago Press, 2017)
Because of their permeable skin, terrestrial amphibians are constantly challenged by the potential risk of dehydration. However, some of the physiological consequences associated with dehydration may affect aspects that are themselves relevant to the regulation of water balance. Accordingly, we examined the effects of graded levels of dehydration on the rates of evaporative water loss and water absorption through the skin in the terrestrial Neotropical toad, Rhinella schneideri. Concomitantly, we monitored the effects of dehydration on the mass of visceral organs; hematocrit and hemoglobin content; plasma osmolality; and plasma concentration of urea, sodium, chloride, and potassium. We found that dehydration caused an increase in the concentration of body fluids, as indicated by virtually all the parameters examined. There was a proportional change in the relative masses of visceral organs, except for the liver and kidneys, which exhibited a decrease in their relative masses greater than the whole-body level of dehydration. Changesor the preservationof relative organ masses during dehydration may be explained by organ-specific physiological adjustments in response to the functional stress introduced by the dehydration itself. As dehydration progressed, evaporative water loss diminished and water reabsorption increased. In both cases, the increase in body fluid concentration associated with the dehydration provided the osmotic driver for these changes in water flux. Additionally, dehydration-induced alterations on the cutaneous barrier may also have contributed to the decrease in water flux. Dehydration, therefore, while posing a considerable challenge on the water balance regulation of anurans, paradoxically facilitates water conservation and absorption.
Keywords: amphibians; Anura; evaporative water loss; rehydration; water balance